Respuesta :

Answer:

a = p * q

b = p * s + q * r

c = r * s

Step-by-step explanation:

In the trinomial ax² + bx + c

a is the coefficient of x²

b is the coefficient of x

c is the numerical term

∵ The trinomial is ax² + bx + c

∵ Its factors are (px + r) and (qx + s)

ax² + bx + c = (px + r)(qx + s)

∵ (px + r)(qx + s) = (px)(qx) + (px)(s) + r(qx) + (r)(s)

∴ (px + r)(qx + s) = pqx² + (psx + qrx) + rs

ax² + bx + c = pqx² + (ps + qr)x + rs

→ By comparing the two sides

∵ ax² = pqx² ⇒ divide both sides by x²

a = pq

∵ bx = (ps + qr)x ⇒ Divide both sides by x

b = ps + qr

c = rs

a = p * q

b = p * s + q * r

c = r * s